Concise synthesis of beta-blockers (S)-metoprolol and (S)-betaxolol using hydrolytic kinetic resolution - Muthukrishnan, Murugan; Garud, Dinesh R.; Joshi, Rohini R.; Joshi, Ramesh A. (Tetrahedron, 2007)
Enantiopure (S)-metoprolol and (S)-betaxolol were prepared in an extremely simple and practical way using Jacobsen's hydrolytic kinetic resolution of terminal epoxides in isopropanol. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: beta-blockers; betaxolol; Hydrolytic kinetic resolution; metoprolol